Oxford handbook of emergency medicine. - Wyatt, Jonathan P.; Taylor, Robert G.; Wit, Kerstin de; Hotton, Emily (Oxford : Oxford University Press, 2020)
'The Oxford Handbook of Emergency Medicine' provides practical, accessible advice on the wide range of situations that present to the emergency department. Precise and prescriptive, it gives up-to-date, step-by-step guidance on presentation, investigation, diagnosis, emergency treatment, and further referral for adult and paediatric patients.
This edition also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 2, 2020).
Keywords: Emergency medicine -- Handbooks, manuals, etc